DIGITAL BANKING: CATALYST OR CHALLENGE? ANALYZING PROFITABILITY AMIDST THE COVID-19 PANDEMIC - Adzimatinur, Fauziyah; Siti Jahidah, Nurul; Rois, Tatang (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2024)
This study investigates the impact of digital banking on banking sector’s profitability during the COVID-19 pandemic. As the pandemic prompted a noticeable decline in banking profitability, the industry responded by hastening the integration of digitalization strategies to align with evolving customer preferences. Focusing on the specific impact of banking digitalization within the pandemic context, the study employs panel data spanning 2017 to 2022 from six conventional commercial banks. The analitycal framework incorporates variables encompassing mobile and internet banking transactions, bank size, economic growth, and a COVID-19-related dummy variable. The study’s banking yielding a positive impact and internet banking showing a negative effect. However, bank size and economic growth do not exhibit statistically significant relationships with profitability. The COVID-19 pandemic negatively affects banking profitability. Even though digital banking initiatives like mobile banking can enhance profitability, significant challenges related to other digital channels such as internet banking remain. The pandemic complicates these dynamics, adaptive and careful approach is highly needed to digital transformation in the banking sector.